Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1002/jbm.b.31754
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, microhardness, and biocompatibility characteristics of yttrium hydroxyapatite doped with fluoride

Abstract: The current study focused on doping of hydroxyapatite (HA) with constant yttrium (Y(3+) ) and varying fluoride (F(-) ) compositions to investigate its microstructure, microhardness, and biocompatibility. HA was synthesized by precipitation method and sintered at 1100°C for 1 h. Y(3+) and F(-) ion dopings resulted in changes in densities. In x-ray diffraction analysis, no secondary phase formation was observed. Lattice parameters decreased upon ion substitutions. Scanning electron microscopy (SEM) results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 47 publications
0
22
0
2
Order By: Relevance
“…Moreover, Y 3+ ions had showed to be able to promote Saos-2 cell proliferation by methylthiazolyldiphenyl-tetrazolium (MTT) assay [276]. Accordingly, Webster et al concluded that Y induces a greater osteoblast adhesion on bulk HAp doped with Y (up to 7 mol%) with respect to pure HAp [72].…”
Section: Influence Of Lnmentioning
confidence: 99%
“…Moreover, Y 3+ ions had showed to be able to promote Saos-2 cell proliferation by methylthiazolyldiphenyl-tetrazolium (MTT) assay [276]. Accordingly, Webster et al concluded that Y induces a greater osteoblast adhesion on bulk HAp doped with Y (up to 7 mol%) with respect to pure HAp [72].…”
Section: Influence Of Lnmentioning
confidence: 99%
“…These structural modifications can alter the solubility, thermal stability, and mechanical properties as well as the in-vitro bioactivity of HA crystals [16][17][18][19]. Over the past decades, many different methods have been introduced for the production of various substituted apatites with precise control of the microstructure, particle shape and size [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about the effects of the new molecular structure formed as a result of the doping (Khan et al, ). The replacement of ions in the nHAp structure with different ions in application area may alter the solubility, thermal stability and mechanical properties of nHAp crystals (Nasiri‐Tabrizi & Fahami, ; Toker et al, ). Therefore, it is important to mimic the body environment in the release study.…”
Section: Resultsmentioning
confidence: 99%